HUBUNGAN SIKAP DAN PERILAKU CARING PERAWAT TERHADAP KEPUASAN PASIEN DI RUANG RAWAT INAP INTERNE RSU MAYJEN H.A THALIB KERINCI TAHUN 2017 - Soviarni, Soviarni (Menara Ilmu, 2019)
Nurse in nursing services appreciate human dignity and prestige,the uniqueness of the patient and unaffected by consideretion, ethnicity, color, age, sex, political and religius flow. Of data that can be in RSU Mayjen H.A Thalib Kerinci. In gretting the number of patients and in 2.070 patients inpatient ward interne. The purpose of this research is to know the relationship of attitude and caring behavior to patient satisfaction in the inpatien room interne RSU Mayjen H.A Thalib Kerinci. The method used in this research is quntitative method with correlation reserch desingn nd approach cross sectional with sampling technique that is akidental sampling counted 94 respondens. The instrument used in a quesionnaire. Data analysis usung chi-square on p < 0,05. The results of the analysis showed that the relationship between attitude and patien satisfaction in interne inpatient room RSU Mayjen H.A Thalib Kerinci, with value p value = 0,000. And the relationship berween caring behavior and patient satisfaction in the interne inpatien room RSU Mayjen H.A Thalib Kerinci, with value p value = 0,000. It is advisable for the hospital to provide input to improve patient satifaction and improve cring behavior of nurses in giving nursing care. Keywords : attitude, caring behavior, patient satisfaction